2022
DOI: 10.3389/fphar.2022.1072651
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in DNA methyltransferase inhibitors as anticancer agents

Abstract: DNA methylation mediated by DNA methyltransferase is an important epigenetic process that regulates gene expression in mammals, which plays a key role in silencing certain genes, such as tumor suppressor genes, in cancer, and it has become a promising therapeutic target for cancer treatment. Similar to other epigenetic targets, DNA methyltransferase can also be modulated by chemical agents. Four agents have already been approved to treat hematological cancers. In order to promote the development of a DNA methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 126 publications
0
14
0
Order By: Relevance
“…When combined with hydralazine, which can also affect DNA methylation, the combined action on chromatin structure and gene regulation may potentiate the cytotoxic effects of doxorubicin ( Fig 2B ) [ 40 ]. The combined effects of doxorubicin and hydralazine on cell cycle progression may lead to enhanced cytotoxicity by preventing cancer cells from repairing DNA damage and proliferating [ 41 ] ( Fig 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…When combined with hydralazine, which can also affect DNA methylation, the combined action on chromatin structure and gene regulation may potentiate the cytotoxic effects of doxorubicin ( Fig 2B ) [ 40 ]. The combined effects of doxorubicin and hydralazine on cell cycle progression may lead to enhanced cytotoxicity by preventing cancer cells from repairing DNA damage and proliferating [ 41 ] ( Fig 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that the promoter region of TEAD4 could be heavily methylated. Therefore, the use of DNA methyltransferase inhibitors (such as decitabine or azacitidine) may be a potential treatment option for certain tumor types [38]. In some tumors, TEAD4-∆N may be overexpressed, making its silencing potentially beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…This is because current DNA methyltransferase inhibitors and TET inhibitors may cause mutations that lead to malformations during embryonic development. A new generation of DNA methylation inhibitors is on the horizon, which may increase their potential use for implantation-related issues [38] in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic silencing of tumor suppressor genes (TSG) is a common hallmark of cancer. This phenomenon has been classically associated to DNA hypermethylation of TSG promoter proximal regions 50 , and has driven the research and implementation of inhibitors of DNA methylation in a wider range of cancer 51 . While an EZH2 inhibitor has been approved for clinical usage 52 , its application is still limited to EZH2 mutated cancers.…”
Section: Discussionmentioning
confidence: 99%